Power Control Algorithm for Throughput Enhancement in Full-Duplex Communications - Lee, Won Jae; Kim, Jae Hyun (International Conference on ICT Convergence, 2020)
Full-duplex (FD) communication transmits and receives packets simultaneously at the same channel. The FD communication is possible thanks to self-interference cancellation (SIC) technology that has developed. However, in the asymmetric FD pair, the interference should be carefully considered to fully utilize FD communication. In this paper, we propose a power control algorithm to improve throughput performance. The access point (AP) controls the transmission power of the AP and the uplink (UL) node. The simulation results show that the throughput performance of the proposed algorithm is higher than that of other algorithms.
Keywords: Access points; Full duplex communication; Full-duplex; Self-interferences; Throughput enhancement; Throughput performance; Transmission power; Full-duplex; medium access control (MAC) protocol; power control; wireless lan (WLAN)